Time-activity budgets and hunting behavior of the Roadside Hawk (Rupornis magnirostris) and the Long-winged Harrier (Circus buffoni) - Baladron Felix, Alejandro Victor (2016)
We conducted a study aimed to evaluate and compare the behavioral patterns of the Roadside Hawk (Rupornis magnirostris) and the Long-winged Harrier (Circus buffoni), two common but poorly known Neotropical raptors. From 2005 to 2008, we quantified the time-activity budgets of both raptors at the Pampas region of Argentina in order to determine their allocation of time to different activities, their foraging strategies and hunting modes, and whether their behavioral patterns change in different habitats and seasons. The Roadside Hawk and the Long-winged Harrier showed dissimilar activity patterns. Hawks devoted more time to perching (45.5% of total time) than harriers (13%), whereas harriers devoted more time to foraging (45%) than hawks (13%). No differences were found in the time they devoted to fly. In addition, both species differed in the use of flying modes, perching sites, and habitat types. Hawks preferably used cruising flights, perched on tall poles or trees, and were found in woodlands and urban areas. Harriers preferably used soaring and circle flights, perched on the ground, and were found in grasslands and agroecosystems. Notwithstanding, the most obvious difference between these raptors were their hunting modes: the Roadside Hawk behaved as a sit-and-wait predator and the Long-winged Harrier as a wide-foraging predator. These patterns seem to be consistent in different habitat contexts and showed certain differences between seasons. Our results suggest that these species may segregate spatially by utilizing different hunting habitats as well as behaviorally, by using different hunting modes.